Comprehensive geriatric care reduces acute perioperative delirium in elderly patients with hip fractures: A meta-analysis. Issue 26 (June 2017) - Wang, Yiyang; Tang, Jun; Zhou, Feiya; Yang, Lei; Wu, Jianbin
Abstract: Background: The aim of the current meta-analysis was to assess the treatment effect of comprehensive geriatric care in reducing acute perioperative delirium in older patients with hip fractures, compared with the effect of a routine orthopedic treatment protocol. Methods: We conducted a search of multiple databases to identify randomized controlled trials (RCTs) and quasi-RCTs comparing comprehensive geriatric care and routine orthopedic treatment regarding the following outcomes: incidence of delirium, assessment of cognitive status, and duration of delirium. Odds ratios (ORs) and mean differences (MDs) were pooled using either a fixed-effects or a random-effects model, depending on the heterogeneity of the trials included in the analysis. Results: Six RCTs and 1 quasi-RCT provided data from 1840 patients. These data revealed that comprehensive geriatric care may reduce the incidence of perioperative delirium (OR = 0.71; 95% confidence interval [CI], 0.57–0.89; P  = .003) and that it was associated with higher cognitive status during hospitalization or at 1 month postoperatively (MD = 1.03; 95% CI, 0.93–1.13; P  ⩽ .00001). There was no significant difference in duration of perioperative delirium between the 2 treatment groups (MD = −2.48; 95% CI, −7.36 to 2.40; P  = .32). Conclusion: Based on the quality of evidence provided, comprehensive geriatric care may reduce the incidence of perioperative delirium. To obtain evidence regarding the merits of comprehensive geriatric care in reducing severity of delirium and shortening the duration of delirium, there is a need for multicenter RCTs with high methodological quality. Abstract : Supplemental Digital Content is available in the text